Cathepsin L and B as Potential Markers for Liver Fibrosis: Insights From Patients and Experimental Models. Issue 6 (June 2017) - Manchanda, Mansi; Das, Prasenjit; Gahlot, Gaurav P S; Singh, Ratnakar; Roeb, Elke; Roderfeld, Martin; Gupta, Siddhartha Datta; Saraya, Anoop; Pandey, R M; Chauhan, Shyam S
Abstract : OBJECTIVES: : Cathepsin L (CTSL) and B (CTSB) have a crucial role in extracellular matrix (ECM) degradation and tissue remodeling, which is a prominent feature of fibrogenesis. The aim of this study was to determine the role and clinical significance of these cathepsins in liver fibrosis. METHODS: : Hepatic histological CTSL and CTSB expression were assessed in experimental models of liver fibrosis, patients with liver cirrhosis, chronic viral hepatitis, and controls by real‐time PCR and immunohistochemistry. Plasma levels of CTSL and CTSB were analyzed in 51 liver cirrhosis patients (Child–Pugh stages A, B and C) and 15 controls. RESULTS: : Significantly enhanced CTSL mRNA ( P =0.02) and protein ( P =0.01) levels were observed in the liver of carbon tetrachloride‐treated mice compared with controls. Similarly, hepatic CTSL and CTSB mRNA levels ( P =0.02) were markedly increased in Abcb4−/− (ATP‐binding cassette transporter knockout) mice compared with wild‐type littermates. Elevated levels of CTSL and CTSB were also found in the liver ( P =0.001) and plasma ( P <0.0001) of patients with hepatic cirrhosis compared with healthy controls. Furthermore, CTSL and CTSB levels correlated well with the hepatic collagen ( r =0.5, P =0.007; r =0.64, P =0.0001). CTSL and CTSB levels increased with the Child–Pugh stage of liver cirrhosis and correlated with total bilirubin content ( r =0.4/0.2; P ≤0.05). CTSL, CTSB, and their combination had a high diagnostic accuracy (area under the curve: 0.91, 0.89 and 0.96, respectively) for distinguishing patients from controls. CONCLUSIONS: : Our data demonstrate the overexpression of CTSL and CTSB in patients and experimental mouse models, suggesting their potential as diagnostic biomarkers for chronic liver diseases.